Ability to Write Poetry Texts for Class X Students at Al Washliyah Pasar Senen High School Using the Time Token Model - Panjaitan, Rohni Sari; Hutagalung, Trisnawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the effect of the Time Token learning model on the ability to write poetry texts in class X of SMA Swasta Al Washliyah Pasar Senen for the 2023/2024 academic year. The population and sample in this study were all students of class X IPA IPS, totaling 24 students with the Time Token model. This research uses a one group pretest-posttest design experimental method using a quantitative approach. The instruments used in this research are the building blocks of writing poetry texts which consist of diction, theme, rhyme/rhythm, figurative language (figure of speech), and message. The data analysis techniques used are analysis requirements tests, normality tests, and hypothesis tests. The research results before using the Time Token model were 62.8 and classified as sufficient. Meanwhile, the research results after using the Time Token model were 73 and classified as good. Based on the results of the hypothesis test, it was found that tcount > ttable, namely 0.0107 > 0.337, so the hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. This proves that there is a significant influence of using the Time Token model on the ability to write poetry in class X SMA Swasta Al Washliyah Pasar Senen Tahun Ajaran 2023/2024.